Polycystic Ovarian Syndrome - Wang, Zhengchao (IntechOpen, 2020)
This book includes two sections: Clinical Features, and Basic Research of Polycystic Ovary Syndrome (PCOS). This book provides a comprehensive overview of latest PCOS research to benefit the population of women with PCOS. We sincerely thank Dr Alsadi Bassim, Prof. Orbetzova Maria, Prof. Abduljabbar Hassan, and Dr Shaobing Wang for their contributions to the section of PCOS clinical features and thank Dr Zhenghong Zhang, Dr Zhengchao Wang, Dr Fan Wang, Prof. Dolžan Vita, and Dr Mohamed-Hussein Zeti-Azura for their contributions to the section of PCOS basic research.At last, we hope that this book is meaningful to the clinicians who care for women with PCOS and to the researchers who investigate the complexities of this disorder.